Aplikasi Penjualan Batik Khas Tangerang Pada CV Ladang Emas Productions - Bangun Suprianto; Irfan Alamsah; Jepri Afrizal; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Ladang Emas Productions is a company engaged in the production and sale of typical Tangerang batik, in carrying out its product sales activities this company still uses a manual method and has not used a web-based software system or technology, namely e-commerce. The research conducted by the author aims to create an application for selling Tangerang typical batik at CV Ladang Emas productions. This sales system was created using the prototype method using HTML, Javascript, Node.js, Express.js, React.jc and mongoDB languages. The results of the development of this sales application can be used practically and effectively in carrying out the sales process and can be used for promotional media.